[Claiming our future ; Coup rumors ; North Andrews [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Looks into the conflict between the townfolk and the logging company on the issue of the environment in Gabaldon, Nueva Ecija. Rumors of a coup continue to fly thick and fast inspite official denials. Interviews with an unconventional disc jockey.